PENGEMBANGAN SUMBER DAYA MANUSIA PADA LEMBAGA PUSAT KARIR DI PERGURUAN TINGGI AGAMA ISLAM NEGERI - YENTI AFRIDA; ROMI ISKANDAR (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The research theme is human resource management. The purpose of this research is to see the importance of career center institution at State Islamic University. The object of research is at the Faculty of Islamic Economics and Business IAIN Imam Bonjol Padang. The type of research is field study. The results of the study are: career center institutions have a very important role at the University.